2016
DOI: 10.1002/pen.24359
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and properties of novel epoxy composites containing electrospun PA6/F‐MWNTs fibers

Abstract: The Nylon 6 (PA6)/the functionalized multiwalled carbon nanotubes (F‐MWNTs) fibrous membranes were fabricated by electrospinning, and then incorporated into an epoxy matrix. Their morphology, thermal stability, mechanical properties, thermal conductivities, and electrical resistivity were investigated. The electrospun PA6/F‐MWNTs fibers performed as a skeleton in the epoxy matrix, and the well interfacial adhesion between the epoxy matrix and the PA6/F‐MWNTs fibers leads to high mechanical properties of compos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…The initial decomposition occurred below 310°C, which was attributed to the irreversible breakage of the urethane linkages. And the second stage from 425°C to 450°C results from the decomposition of HSG side chain . It indicated that the thermal stabilities of the PU/HSG nanofibers were gradually improved with the increasing amount of HSG .…”
Section: Resultsmentioning
confidence: 97%
“…The initial decomposition occurred below 310°C, which was attributed to the irreversible breakage of the urethane linkages. And the second stage from 425°C to 450°C results from the decomposition of HSG side chain . It indicated that the thermal stabilities of the PU/HSG nanofibers were gradually improved with the increasing amount of HSG .…”
Section: Resultsmentioning
confidence: 97%
“…In [122,123] CNTs are added into PU nanofibers, and interleaved into epoxy-basal composite, registering 13% increase in tensile and 17.3% in flexural strength compared to neat material, addressing the improvements to an enhanced fiber-resin adhesion. In [124] CNTs are added into PA nanofibers and embedded into pure resin: resin with 3% of MWCNT-PA nanofibers (in which the CNT accounted for the 1% in mass) led to improvements of modulus of elasticity, elongation at break and tensile strength of 690, 51 and 239%, respectively. Authors addressed the improvements to the uniform distribution, alignment states and well interfacial adhesion between the nanofibers, the MWNTs and the epoxy matrix, the PA6 serves as an intermediate layer and alleviates the modulus mismatch between the stiff MWNTs and the softer epoxy matrix.…”
Section: Nanofibers Doped With Cntmentioning
confidence: 99%
“…Liao et al fabricated a MWCNT reinforced nylon 6 nanofibers to be impregnated with epoxy and conduct single cantilever assisted dynamic mechanical analysis (DMA) Nylon 6/MWCNT concentration varied from 1 to 3 wt% of epoxy. [ 17 ] Storage modulus of nanocomposites increased steadily with increment in nanofiber weight percentage demonstrating the stiffening effect of nanofibers. Meanwhile, the glass transition temperatures of pure epoxy matrix and epoxy composites with 1, 2, and 3 wt% of composite nanofibers were determined as 24.25, 29.93, 32.37, and 31.21°C, respectively.…”
Section: Introductionmentioning
confidence: 99%